Strategic Roles of Customer Satisfaction Toward the Service Quality at Telekom Malaysia Berhad in Kedah - Shuib, Rusmuna (2011)
The main objective of this study was to examine the relationship between service quality, price and product towards the customer satisfaction of the fixed telephone line at Telekom Malaysia. Research instruments that were used to obtain the data are questionnaire. A total of 101 respondents were randomly selected from the total population of customers in the Region of Kedah. The data was analyzed by “Statistical Package for Social Science” (SPSS Window) Version 16. The tests involved are reliability, Pearson Correlation Coefficient and Multiple Regression. The findings of the study show that the majority of the respondents are from the age of 34 years and above and 38.3 percent of the respondents have been working for more than ten years. Generally, the results of the relationship of service quality and product supported the hypotheses. The strongest facet influenced customer satisfaction of Telekom Malaysia is service quality. That means, the service quality plays an important roles in satisfying customer needs and wants.